Prevalence of migraine in patients of allergic rhinitis - Pai, Sunil; Rosario, David D. M. (International Journal of Research in Medical Sciences, 2018)
Background: Migraine and allergic rhinitis are common disorders. Studies have shown increased frequency of migraine headaches in patients with allergic rhinitis. The aim of this study is to identify how age, sex and degree of allergic sensitization influences the occurrence, severity and treatment outcome of migraine headaches in patients with allergic rhinitis. Methods: The study was conducted between 2014 and 2018 in a tertiary care hospital. 150 patients diagnosed with allergic rhinitis clinically were selected and total serum IgE levels were estimated. These patients were subjected to a detailed history taking to determine the characteristics of headache. All classifiable headache diagnoses had met criteria of the International Classification of Headache Disorders-II-2004. Severity of headache was assessed based on MIDAS score. The data was accessed based on age, sex, serum IgE levels, frequency and severity of migraine attacks and the treatment outcome using statistical methods. Results: The prevalence of migraine in this study was 68% among those who had allergic rhinitis. In this study out 150 patients 111 were females and 39 were males. Comparatively females’ patients 84 (75.7%) were found to be more prone for migraine. Majority patients were in the age group of 20 to 40 years (cumulative percentage of 67.3%). There was a negative correlation between age and IgE levels with r= -0.092. In comparison patients with higher levels of IgE (mean 3633) had more severe headaches. Patients with higher levels of IgE required a longer duration of treatment. Conclusions: This study shows that allergic rhinitis is a risk factor for development of migraine. Apart from high prevalence of migraine in patients with allergic rhinitis it is evident from the study that female sex, younger age group and high degree of allergic sensitization also play an important role as the severity of migraine and treatment course depend on these parameters. Hence the treatment for migraine in patients should aim at reducing the allergic sensitization in addition to concurrent treatment for migraine.